Genotype environment interaction in wheat forage fractions in three samplings - Ramírez Pérez, Luz Oralia; Zamora Villa, Víctor Manuel; Colín Rico, Modesto; De León Castillo, Humberto (Revista Mexicana de Ciencias Agrícolas, 2021)
Winter cereals have useful characteristics for forage production and generally have adequate nutritional quality. In the generation of new varieties, it is necessary to quantify the environmental genotype interaction (IGA) to make a more efficient selection. The objectives were to analyze the genotype environmental interaction (IGA) in forage fractions of 22 lines of beardless wheats and three commercial witnesses of another species, through three samplings. A random complete block design was used with three repetitions in four environments, sampling at 75, 90 and 105 days after planting. The production of total dry forage and its fractions was determined, analyzing them using the AMMI model. The results indicated that thirteen wheat lines together with barley had desirable characteristics to produce total dry fodder through sampling carried out according to superiority over the general average. The oat witness was considered the least productive. The portion of stems was the one with the highest contribution to the dry fodder yield, followed by the leaves and spikes. There was a presence of the IGA in the forage fractions, as well as in the total.
Keywords: AMMI model; fodder fractions; dry fodder; stability; wheats without edge